Risk factors of pulmonary tuberculosis: A community-based case control study - Kokiwar, Prashant Ramdas (Indian Journal of Community Health, 2021)
Studies on risk factors of tuberculosis help to focus on risk of tuberculosis and take appropriate policy action which help to eliminate tuberculosis. Hence present study was carried out to study risk factors of pulmonary tuberculosis. Community-based case-control studywas carried out among 78 age and sex matched cases and controls. Cases were incident cases of pulmonary tuberculosis aged 18-45 years of either sex. Data on housing condition was recorded with direct observation. Cases and controls were comparable for age, sex, presence of diabetes, HIV and immuno-compromised status. Mean body mass index was significantly low in cases as compared to controls (18.06 vs. 22.05; p<0.0001). On binomial logistic regression odds of tuberculosis was 5.544 (95%CI=2.513-12.232; P=0.000) among those exposed to indoor air pollution after controlling for other factors. We conclude that exposure to indoor air pollution was significantly associated with risk of pulmonary tuberculosis